2021
DOI: 10.3390/pathogens10111427
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intraspecies Variability on Growth Rate and Cellular Metabolic Activity of Bacteria Exposed to Rotating Magnetic Field

Abstract: Majority of research on the influence of magnetic fields on microorganisms has been carried out with the use of different species or different groups of microorganisms, but not with the use of different strains belonging to one species. The purpose of the present study was to assess the effect of rotating magnetic fields (RMF) of 5 and 50 Hz on the growth and cellular metabolic activity of eight species of bacteria: Staphylococcus aureus, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae, Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…The results of basic microbiological studies presented in this article were an extension of the previous studies in this area presented in the cited reference works [ 34 , 35 , 37 , 38 , 39 , 40 ]. The cited experimental studies were focused on the influence of the interaction between RMF and antibiotics, as well as the analysis of bacterial colony growth dynamics, the metabolic activity of cells, as well as genetic activity of selected bacterial species exposed to RMF.…”
Section: Discussionsupporting
confidence: 61%
“…The results of basic microbiological studies presented in this article were an extension of the previous studies in this area presented in the cited reference works [ 34 , 35 , 37 , 38 , 39 , 40 ]. The cited experimental studies were focused on the influence of the interaction between RMF and antibiotics, as well as the analysis of bacterial colony growth dynamics, the metabolic activity of cells, as well as genetic activity of selected bacterial species exposed to RMF.…”
Section: Discussionsupporting
confidence: 61%
“…There were also no statistically significant differences in the viability of RMF-exposed cells forming a biofilm on the specific (C, M, B) agar discs. In our previous studies, we showed that the RMF affected the cell viability of S. aureus and P. aeruginosa , but it has to be underlined that these studies were conducted for bacteria cultured in liquid cultures, during their phase of logarithmic growth 18 . In the present study, the exposed bacteria were immobilized on the surface of agar discs and anchored within the biofilm matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of biofilm to the RMF was carried out using self-designed RMF bioreactors, described in our previous works 18 , 20 , 21 , and adopted for purposes of this research. One of the bioreactors was operated with the active RMF generator, while the second served as the control setup (without RMF).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is valid not only because of the aforementioned activity mechanism of these antiseptics, but also because of the rheological phenomena occurring during antiseptics’ introduction, removal and subsequent laboratory stages of dye introduction and microplate well rinsing. As was observed, the measured thickness of staphylococcal biofilms differed not only between particular strains, showing explicitly the importance of intra-species variability [19] , but also within a single sample (well of a 24-well microplate). This thickness differentiation is meaningful, taking into consideration the activity of antiseptics against biofilm.…”
Section: Discussionmentioning
confidence: 83%